Testing of security steel mesh on mosquito prevention - Chanbang,Y. (Chiang Mai University, 2015)
Using screen doors and windows is one of common environmentally friendly insect control measures as an alternative to insecticide use. The objective of this study is to evaluate the effectiveness of security steel mesh produced for screen doors and windows against dengue fever mosquito, Aedes aegypti (Diptera: Culicidae). In experiment 1, the test arena composed of the 2-partition cage separated with 4 types of the steel mesh count: per inch: 14x17 (normal screen), 16x16, 11x10.5 and 8x8 openings with the weft and warp wire at diameter of 1.8 mm. Mosquitoes were released in one side of insect cage, the other side was empty. The result showed that mosquitoes could not penetrate through all steel mesh except on 8x8 openings, with 0.58% of mosquitoes found in the other side. In experiment 2, two mice were introduced in the opposite side of insect releasing in with the test arena as insect attractant. The result found that with the normal screen no mosquito penetrated through the mice side, while in the security steel mesh at 16x16 and 11x10.5 opening found that 1.00 and 0.50% of mosquitoes penetrated through mice side 72-h after releasing. In experiment 3, a rabbit was used as an insect attractant. The rank order of mesh size that number of mosquitoes penetrated through the tested screens to the rabbit side was 14x17 = 16x16>11x10.5, and 8x8. The findings revealed that the security steel mesh with wire 16x16 can be used to prevent blood feeding Ae. aegypti mosquitoes with the same effect as normal screens in laboratory conditions.